The role of contrast-enhanced ultrasound (CEUS) in visualizing atherosclerotic carotid plaque vulnerability: Which injection protocol? Which scanning technique?. Issue 5 (May 2015) - Iezzi, Roberto; Petrone, Gianluigi; Ferrante, Angela; Lauriola, Libero; Vincenzoni, Claudio; la Torre, Michele Fabio; Snider, Francesco; Rindi, Guido; Bonomo, Lorenzo
Highlights: CEUS is a safe and efficacious technique for the identification and characterization of carotid plaque. CEUS represents a diagnostic tool for the management of patients with carotid plaque, particularly in asymptomatic patients. Improved diagnostic performance is achieved with the injection of 4 mL bolus of contrast-medium. Improved diagnostic performance is achieved with the use of Dynamic Imaging rather than late-phase imaging. Abstract: Purpose: To correlate the degree of plaque vulnerability as determined by contrast-enhanced ultrasound (CEUS) with histological findings. Secondary objectives were to optimize the CEUS acquisition technique and image evaluation methods. Materials and methods: Fifty consecutive patients, either symptomatic and asymptomatic referring to our department in order to perform carotid endarterectomy (TEA), were enrolled. Each patient provided informed consent before undergoing CEUS. Ultrasound examination was performed using high-frequency (8–14 MHz) linear probe and a non-linear pulse inversion technique (mechanical index: 0.09–1.3). A double contrast media injection (Sonovue, 2 mL and 4 mL; Bracco, Italy) was performed. Two videotapes were recorded for every injection: early "dynamic" phase and late "flash" phase, performed with 6 high mechanical index impulses. Movies were quantitatively and qualitatively evaluated. Qualitative and quantitative evaluation were statistically compared to immunohistological diagnosis of vulnerable plaque, considered as gold standard. Results: Qualitative CEUS evaluation obtained high statistical results when compared to immunohistological results, with values of sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and diagnostic accuracy of 94%, 68%, 87%, 85% and 86%, respectively, which became higher if considering only asymptomatic patient, with a NPV of 91%. Nevertheless, quantitative software evaluation proved less effective and could not reach similar results. Conclusion: Carotid plaque enhancement assessed with CEUS well correlates with histological assessment of plaque instability. CEUS may provide valuable information for plaque risk stratification and may play a role in the indication to treatment of patients with carotid stenoses, particularly in asymptomatic population.